PHYTOCHEMICAL SCREENING AND ANTIMICROBIAL ACTIVITY OF AZADIRACHTA INDICA AND PLECTRANTHUS AMBOINICUS EXTRACT - S., GEJALAKSHMI; SENTHILRAJ, R.; A., TANISHA B.; S., SRUTHI; M., THARUN KUMAR (International Journal of Current Pharmaceutical Research, 2020)
Objective: In the present research, a clear systematic investigation of phytochemical screening and antibacterial activity of herbal plants such as Azadirachta indica and Plectranthus amboinicus has been carried out. Methods: The aqueous and alcoholic extract was prepared in soxhlet apparatus and phytochemical analysis of extracts was performed and analysed. The in vitro antimicrobial activity was performed by cup plate method. These extracts were studied under agar diffusion method against three bacterial species such as Bacillussubtills, Staphylococcus aureus, and Escherichia coli at 5µg, 50 µg and 250 µg concentration. Results: The combine extract showed a predominant activity against these bacteria, which confirmed antimicrobial activity in AEAI and AEPA Conclusion: The results obtained in this study clearly indicate that AEAI and AEPA has a significant potential to use as an antimicrobial agent